The Role of School Leadership in Developing Creativity among Teachers of the Basic Stage (Public schools in Tubas Province model) - Alghwanmeh, Rawan AbdAlkareem (Journal of Educational and Psychological Sciences, 2023)
This study aimed to identify the role of school leadership in the development of creativity among teachers of basic public schools in Tubas Governorate from the point of view of the teachers themselves has used the descriptive analytical approach, while the study tool questionnaire, and the study community may have reached the community (806) teachers where (260) teachers were selected in a simple random way where each of the ranks of a teacher was chosen, while the rate of recovery of valid papers (96%), and his actual sample (240) single any teacher and teacher The most important results of the study where the appreciation of the role of school leadership a prominent role came with a high degree of appreciation while the relative weight of the target group (74%) while the most important results of the study indicated that the role of school leadership on the development of creativity among students of the basic stage in Tubas Governorate has come with a relative weight (74%) and a high degree of appreciation, has been the role of school leadership in the development of creativity as a concept for teachers of primary stage schools in Tubas Governorate of The teachers’ point of view was high, so the arithmetic mean was (3.65) and the relative weight (70.8%), and the role of school leadership in motivating primary stage teachers towards creativity was also high, as the arithmetic mean (3.65) and relative weight (73.05%). In addition to the field of creativity development (other factors affecting creativity) among teachers of basic government schools, the role of school leadership was high, as the arithmetic average came (3.56) and the relative weight (71.3%) and finally the dependent variable creativity and its skills were high, so the arithmetic average was (3.71) and the relative weight (74.21%) while the level of significance was less than (0.05), which means that there are statistically significant differences between the role of school leadership and the development of creativity among primary school teachers, which are attributed to Demographic factors (gender variable in favor of (females), and variable of scientific qualification in favor of master’s The variable of years of experience was the difference in favor of 21 years or more, and the conclusion of the study is that there is support for the school leadership for teachers by providing available material capabilities, while increasing the role of school leadership in communicating with educational directorates while providing creativity.